Reshaping agrifood systems to achieve multiple development goals - Fan, Shenggen; Otsuka, Keijiro (International Food Policy Research Institute, 2021)
Today, agrifood systems are undergoing remarkable changes, reflected in the modernization of food value chains and rural transformation responding to urbanization, income growth, and expansion of international trade. At the same time, agrifood systems are expected to contribute to a wide range of development goals, reaching beyond agricultural productivity growth and food security. Thus this book has examined key issues using new lenses reflecting the rapidly changing world, such as nutrition, household decision-making behavior (related not only to gender but also to credit and insurance), natural resource management (including land, forests, and water), climate change, reprioritization of agricultural research, and political economy. Major findings from regional chapters (Chapters 3–7) were summarized in Chapter 8, while this chapter aims to synthesize the thematic chapters (Chapters 9–21). We highlight priority areas for action to reshape agrifood systems for achieving multiple development goals, including reductions in poverty and malnutrition, without harming the environment.